305 Dopamine Reduces White Matter Injury in Hypoxic-Ischaemia in the Preterm Lamb. (October 2012) - Wong, F; Cassimally, K; Azhan, A; Samarasinghe, T; Nitsos, I; Walker, A; Walker, D
Abstract : Background: Dopamine is frequently used as inotropic agent in preterm infants. Its cardiovascular actions, as well as effects on neurovascular interactions may be neuroprotective during hypoxic-ischaemic events. Using a preterm lamb model we aimed to test the impact of intravenous dopamine on hypoxic-ischaemic brain injury. Method: Nine fetal lambs (91–93d gestation) were instrumented with catheters in carotid artery and jugular vein, and an umbilical cord occluder. Four days after surgery, intravenous dopamine (DA, 10 µg/kg/min, n=5) (or saline, n=4) was commenced. then a hypoxic-ischaemic insult was induced with umbilical cord occlusion for 25 mins. Infusions were continued for another 72 hours before euthanasia. Fetal brains were collected for immunohistopathology. Results: Dopamine infusion increased fetal heart rate (184±1 to 203±1 bpm, p<0.05) while arterial pressure was unchanged. Three animals in the DA group showed tachycardic response to cord occlusion, while the other two animals showed bradycardic response similar to the saline group. In the periventricular white matter, the saline group had higher number of microglia (lectin positive) than the DA group (10±3 vs 6±2 per 0.04mm 2, p<0.05). The saline group tended to have shorter myelinated fibre lengths (CNPase) compared with the DA group (15.0±2.0 vs 18.4±5.7µm respectively, p=ns). No histological differences were evident between DA animals exhibiting a tachycardic or bradycardic response during cord occlusion. Conclusions: Intravenous dopamine reduces hypoxic-ischaemic white matter injury in preterm lambs, independent of the cardiovascular response during the hypoxic-ischaemia.